Novas espécies de Aglaoschema Napp, 1994 (Coleoptera, Cerambycidae) - Napp, Dilma Solange (Papéis Avulsos de Zoologia, 2008)
New species of Aglaoschema Napp, 1994 (Coleoptera, Cerambycidae). New species described from South America: Aglaoschema rondoniense sp. nov. and A. mimos from Brazil (Rondônia), A. acauna from Brazil (Pará), and A. potiguassu from Argentina (Chaco).A key to species, partially modified from Napp (2007) to include the new species, is added.